2012
DOI: 10.2172/1046330
|View full text |Cite
|
Sign up to set email alerts
|

National Geo-Database for Biofuel Simulations and Regional Analysis of Biorefinery Siting Based on Cellulosic Feedstock Grown on Marginal Lands

Abstract: Executive SummaryThe goal of this project undertaken by GLBRC (Great Lakes Bioenergy Research Center) Area 4 (Sustainability) modelers is to develop a national capability to model feedstock supply, ethanol production, and biogeochemical impacts of cellulosic biofuels. The results of this project contribute to sustainability goals of the GLBRC; i.e. to contribute to developing a sustainable bioenergy economy: one that is profitable to farmers and refiners, acceptable to society, and environmentally sound. A sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…In typical eastern-type El Niño events, that is, the tropical Pacific warming region is mainly located in the tropical eastern Pacific region, and the probability of El Niño events is getting smaller and smaller, while another kind of warming region is mainly located in the equatorial central Pacific near the sun line, but the warming phenomenon is occurring more and more frequently [15]. Many scholars have noticed the change of El Niño, a warming area, and call the El Niño event located in the equatorial central Pacific region as the central El Niño event [16], or the El Niño event at the solar boundary [17], or E1 Niño Modoki [15], or the warm pool El Niño event [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In typical eastern-type El Niño events, that is, the tropical Pacific warming region is mainly located in the tropical eastern Pacific region, and the probability of El Niño events is getting smaller and smaller, while another kind of warming region is mainly located in the equatorial central Pacific near the sun line, but the warming phenomenon is occurring more and more frequently [15]. Many scholars have noticed the change of El Niño, a warming area, and call the El Niño event located in the equatorial central Pacific region as the central El Niño event [16], or the El Niño event at the solar boundary [17], or E1 Niño Modoki [15], or the warm pool El Niño event [18].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has also attracted extensive attention of scientists. Since Weng et al [17] pointed out that the frequency of central El Niño events increased significantly after the 1990s, there are more and more international studies on the impact of different distribution types of El Niño events on climate anomalies. For example, some scientists have concluded that the impact of the central El Niño event on the climate of the west coast of North America, South America, and even Japan and New Zealand may be completely opposite to the impact of the eastern El Niño event [19][20][21].…”
Section: Introductionmentioning
confidence: 99%